Radiation Exposure in the Neonatal Intensive Care Unit in Newborns and Staff - Cakir, Salih Cagri; Dorum, Bayram Ali; Koksal, Nilgun; Ozkan, Hilal; Yazici, Zeynep; Parlak, Mufit; Gulleroglu, Nadide Basak (American Journal of Perinatology, 2021)
Objective Portable X-rays remain one of the most frequently used diagnostic procedures in neonatal intensive care units (NICU). Premature infants are more sensitive to radiation-induced harmful effects. Dangers from diagnostic radiation can occur with stochastic effects. We aimed to determine the radiation exposure in premature infants and staff and determine the scattering during X-ray examinations in the NICU.Study Design In this prospective study, dosimeters were placed on premature infants who were ≤1,250 g at birth and ≤30 weeks of gestational age who stayed in the NICU for at least 4 weeks. The doses were measured at each X-ray examination during their stay. The measurements of the nurses and the doctors in the NICU were also performed with dosimeters over the 1-month period. Other dosimeters were placed in certain areas outside the incubator and the results were obtained after 1 month.Results The mean radiation exposure of the 10 premature infants, monitored with dosimeters, was 3.65 ± 2.44 mGy. The mean skin dose of the six staff was 0.087 ± 0.0998 mSV. The mean scattered dose was 67.9 ± 26.5 µGy.Conclusion Relatively high exposures were observed in 90% of the patients and two staff. The radiation exposure levels of premature infants and staff may need to be monitored continuously.Key Points
Keywords: bedside X-ray; neonatal intensive care unit; newborn; radiation exposure; staff safety